Interaction of Er,Cr:YSGG laser with dental hard tissue - Abbas Majdabadi; Mona Ahadi; Reza Fekr Azad (Tehran University of Medical Sciences, 2016)
Background and Aims: Nowadays lasers are used as alternatives to the tooth preparation because of reducing pain, bloodshed and stress. The aim of this study was to observe the effect of Er,Cr:YSGG laser on the dental hard tissues. Materials and Methods: For this studty, molar teeth with no caries or dental restoration and enamel cracks were used. The laser power were taken from 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5 up to 6 Watts for enamel and 0.5, 1, 1.5, 2, 2.5, 3, 3.5 and 4 Watts for dentine simultaneously with water spray. The ablation effect was observed on both enamel and dentine. Finally, by use of a CCD camera connected to the computer, the dimensions of ablated areas were measured and results were applied in graphs. Results: Volume of ablation was increased by increasing laser power. Also, by increasing energy value in each stage, the depth of ablation was increased for enamel and dentine. SEM images of ablations by 3.5 and 4 Watts on enamel and 1 and 1.5 Watts on dentine did not show any sharp edges. Conclusion: The ablation volumes and depth increased by increasing the energy of laser pulses power. The reason for this trend was due to the water spray while irradiating and good absorption of water by laser beam.